2015
DOI: 10.1016/j.chemgeo.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of calcite dissolution in CO2-saturated water at temperatures between (323 and 373) K and pressures up to 13.8 MPa

Abstract: We report measurements of the calcite dissolution rate in CO2-saturated water at pressures ranging from (6.0 to 13.8) MPa and temperatures from (323 to 373) K. The rate of calcite dissolution in HCl(aq) at temperatures from (298 to 353) K was also measured at ambient pressure with pH between 2.0 and 3.3. A specially-designed batch reactor system, implementing a rotating disc technique, was used to obtain the dissolution rate at the solid/liquid interface of a single crystal, free of mass transfer effects. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 63 publications
(122 reference statements)
5
80
0
Order By: Relevance
“…4.7 presents the calculated concentration of calcium in the CO 2 saturated water while calcite continuously dissolves. These calculations were compared with the experimental measurements of Peng et al (2014) at T ¼ 353 K and P ¼ 13:8 MPa. It can be seen that a good accuracy is achieved for the period of time between 5 min and 1 h for which experimental measurements were available.…”
Section: Kinetic Modelling Of Pure Calcite Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.7 presents the calculated concentration of calcium in the CO 2 saturated water while calcite continuously dissolves. These calculations were compared with the experimental measurements of Peng et al (2014) at T ¼ 353 K and P ¼ 13:8 MPa. It can be seen that a good accuracy is achieved for the period of time between 5 min and 1 h for which experimental measurements were available.…”
Section: Kinetic Modelling Of Pure Calcite Dissolutionmentioning
confidence: 99%
“…Peng et al (2014) recently determined the dissolution rates of calcite in CO 2 saturated waters far from equilibrium. The following major parallel reactions were taken into account in their study: CaCO 3 ðsÞ þ H þ À!…”
Section: Kinetic Modelling Of Pure Calcite Dissolutionmentioning
confidence: 99%
“…The rotational angular velocity of the sample was maintained at 73 s -1 for both analogue samples in order to eliminate mass-transfer effects. It was observed that the dissolution profiles for Ketton limestone and North Sea Chalk follow the same trends as found for single calcite crystals (4). The reactive surface area of the sample was obtained by subtracting the pore area from the geometric surface area.…”
Section: Dissolution Of Carbonate Reservoir Analogue Minerals In the mentioning
confidence: 99%
“…For each set of measurements, using the rotating disk technique, the angular velocities were increased until a regime where reaction rates were independent of transport limitation was found, as described by Peng et al (4). For calcite, chalk and limestone, allowance was made for variation in pH as the mineral dissolved, according to the software PHREEQC version 3.1.4 (22), but for dolomite and magnesite pH changes were estimated to be negligible.…”
Section: Initial Reaction Rates For Carbonate Minerals In Co2-acidifimentioning
confidence: 99%
See 1 more Smart Citation